A scoping review of the exercise performance and thermoregulatory response to menthol cooling strategy in hot and humid environment - Hazman, Siti Nurhusna ‘Aqilah (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2021)
Background/Aim: Cooling strategy had been studied since many years ago and had been proven to be beneficial for athletes. Menthol has been documented as a cooling strategy to enhance exercise performance during hot and humid environment. This scoping review aims to synthesis the previous findings on menthol cooling strategy in thermally stress condition to exercise performance, body core and skin temperature and heart rate responses. Method: The literatures were obtained from PubMed, ResearchGate, ProQuest, Scopus, ScienceDirect, and SpringerLink ranging from year 2015 until 2021. Results: Thirteen publications were included and reviewed. Among the studies, seven (53.8%) articles investigated on menthol rinse/swill, two (15.4%) articles studied on menthol ingestion, and one (7.7%) article investigated combination of menthol spray, menthol skin application, garment soaked with menthol and menthol body immersion. Available evidence suggested that menthol cooling strategy confers benefits to exercise performance by menthol mouth rinse, ingestion, and menthol immersion during exercise in thermally stressed condition. However, menthol cooling strategy did not attenuate changes in core and skin temperature and heart rate responses. Conclusion: Available evidence suggests that menthol cooling strategy during exercise in a hot and humid environment could improve exercise performance and warrants further investigation.